2021
DOI: 10.1159/000512954
|View full text |Cite
|
Sign up to set email alerts
|

Screening Status as a Determinant of Choice of Colorectal Cancer Screening Method: A Population-Based Informed Survey

Abstract: Objectives: Fecal blood testing is a noninvasive alternative to colonoscopy for colorectal cancer (CRC) screening and is preferred by a substantial proportion of individuals. However, participant-related determinants of the choice of screening method, particularly up-to-date screening status, remain less studied. We aimed to determine if up-to-date screening status was related to choosing a fecal blood test over colonoscopy. Setting: Participants in the population-based cross-sectional survey study Bus Santé i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In the same study, regardless of the test chosen based on one's preference, up to 80% of those screened were screened with colonoscopy. The two studies by Palmer et al (2010) [47] and Sandoval et al (2021) [48] also showed that individuals who were adherent to CRC screening were more likely to choose colonoscopy as their preferred test, while those who were non-adherent to CRC screening were more likely to choose stool-based tests. Participants with up-to-date screening were more concerned about test accuracy, unlike participants without up-to-date screening who were more concerned about the risks of colonoscopy and its costs [48].…”
Section: Intention To Participate and Actual Participation In Relation To The Stated Preferencementioning
confidence: 96%
See 3 more Smart Citations
“…In the same study, regardless of the test chosen based on one's preference, up to 80% of those screened were screened with colonoscopy. The two studies by Palmer et al (2010) [47] and Sandoval et al (2021) [48] also showed that individuals who were adherent to CRC screening were more likely to choose colonoscopy as their preferred test, while those who were non-adherent to CRC screening were more likely to choose stool-based tests. Participants with up-to-date screening were more concerned about test accuracy, unlike participants without up-to-date screening who were more concerned about the risks of colonoscopy and its costs [48].…”
Section: Intention To Participate and Actual Participation In Relation To The Stated Preferencementioning
confidence: 96%
“…There are two prominent trends in population preference for CRC screening tests reported in previous studies: people preferred either the most accurate test (visual or structural test: colonoscopy) [29,31,[41][42][43][44][45][46][47][48][49][50][51] or the least invasive one (stool-based test: fecal occult blood test (FOBT) or stool DNA (sDNA) test) [26,28,[52][53][54][55][56][57][58]. While both tests are highly recommended by international guidelines [5][6][7][8], with colonoscopy recommended as the gold standard test and stool-based test (iFOBT or gFOBT) as the standard firstline test for population-based CRC screening, population preference for colonoscopy and stool-based tests, as well as the other available screening techniques, has not been systematically reviewed.…”
Section: Population Preference For Crc Screening Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Un bus recherche est utilisé à Genève depuis 1992 pour réaliser des études principalement épidémiologiques, telles que l'étude décrite par Sandoval 2021 [6]. Ces unités mobiles de recherche peuvent avoir des équipements et des fonctions variables et permettent de pallier les espaces insuffisants de nombreux cabinets médicaux, apporter du temps pour le médecin généraliste avec une équipe mobile dotée d'un médecin en capacité d'informer les patients, de recueillir leur consentement,…”
Section: Permettre à La Recherche D'aller Vers Le Patient : éQuipes E...unclassified